Robustness of the Blandford-Znajek mechanism - Palenzuela, Carlos (2011)
The Blandford–Znajek (BZ) mechanism has long been regarded as a key ingredient in models attempting to explain powerful jets in AGNs, quasars, blazzars, etc. In such a mechanism, energy is extracted from a rotating black hole and dissipated at a load at far distances. In this work we examine the behavior of the BZ mechanism with respect to different boundary conditions, revealing the robustness of the mechanism upon variation of these conditions. Consequently, this work closes a gap in our understanding of this important scenario.